Injectable thermosensitive chitosan/gelatin hydrogel for dental pulp stem cells proliferation and differentiation - Mohammad Samiei; Elaheh Dalir Abdollahinia; Nazanin Amiryaghoubi; Marziyeh Fathi; Jaleh Barar; Yadollah Omidi (BioImpacts, 2023)
Introduction: Biocompatible and biodegradable scaffolds based on natural polymers such as gelatin and chitosan (CS) provide suitable microenvironments in dental tissue engineering. In the present study, we report on the synthesis of injectable thermosensitive hydrogel (PNIPAAm-g-CS copolymer/gelatin hybrid hydrogel) for osteogenic differentiation of human dental pulp stem cells (hDPSCs). Methods: The CS-g-PNIPAAm was synthesized using the reaction of carboxyl terminated PNIPAAm with CS, which was then mixed with various amounts of gelatin solution in the presence of genipin as a chemical crosslinker to gain a homogenous solution. The chemical composition and microstructures of the fabricated hydrogels were confirmed by FT-IR and SEM analysis, respectively. To evaluate the mechanical properties (e.g., storage and loss modulus of the gels), the rheological analysis was considered. Calcium deposition and ALP activity of DPSCs were carried out using alizarin red staining and ALP test. While the live/dead assay was performed to study its toxicity, the real-time PCR was conducted to investigate the osteogenic differentiation of hDPSCs cultured on prepared hydrogels. Results: The hydrogels with higher gelatin incorporation showed a slightly looser network compared to the other ones. The hydrogel with less gelatin indicates a rather higher value of G', indicating a higher elasticity due to more crosslinking reaction of amine groups of CS via a covalent bond with genipin. All the hydrogels contained viable cells with negligible dead cells, indicating the high biocompatibility of the prepared hydrogels for hDPSCs. The quantitative results of alizarin red staining displayed a significant rise in calcium deposition in hDPSCs cultured on prepared hydrogels after 21 days. Further, hDPSCs cultured on hydrogel with more gelatin displayed the most ALP activity. The expression of late osteogenic genes such as OCN and BMP-2 were respectively 6 and 4 times higher on the hydrogel with more gelatin than the control group after 21 days. Conclusion: The prepared PNIPAAm-g-CS copolymer/gelatin hybrid hydrogel presented great features (e.g., porous structure, suitable rheological behavior, and improved cell viability), and resulted in osteogenic differentiation necessary for dental tissue engineering.